1979
DOI: 10.1177/004051757904900910
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Parameters of Cotton Fibers

Abstract: A rapid, accurate method of evaluating cross-sectional parameters of cotton fibers was developed. The effects of swotting cotton while slack or under tension with various agents were ascertained from the resulting data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Mercerization converts the crystal structure of cellulose I to cellulose II and reverses the cellulose chain packing polarity from parallel to antiparallel which is a structural hallmark of this process (Nevell and Zeronian 1985;Wertz et al 2011). Previous studies (Tripp et al 1954;Rollins 1954;Hebert et al 1979) have shown that upon mercerization with caustic soda cotton fiber length shrinks and the diameter increases. In addition the cross section of the fiber becomes more circular.…”
Section: Resultsmentioning
confidence: 99%
“…Mercerization converts the crystal structure of cellulose I to cellulose II and reverses the cellulose chain packing polarity from parallel to antiparallel which is a structural hallmark of this process (Nevell and Zeronian 1985;Wertz et al 2011). Previous studies (Tripp et al 1954;Rollins 1954;Hebert et al 1979) have shown that upon mercerization with caustic soda cotton fiber length shrinks and the diameter increases. In addition the cross section of the fiber becomes more circular.…”
Section: Resultsmentioning
confidence: 99%
“…Several cotton cultivars representing approximately one half of the American cotton crop and offering a wide range in fiber perimeter were grown under identical environmental conditions [9]. The samples were field dried, hand harvested, and of similar maturity.…”
Section: Methodsmentioning
confidence: 99%
“…Fiber perimeter measurements followed the technique published previously [9]. All nep counts were compared with the results of the one gram test in an attempt to predict potential neppiness.…”
Section: Methodsmentioning
confidence: 99%
“…Berlin et al (1981), Hebert et al (1979), thibodeaux and evans (1986), Xu et al (1993), Schneider and retting (1999), and many other researchers have worked on identifying and measuring different characteristics of fibre cross-sections. There are different approaches to analysing the cross-section of fibres.…”
Section: Fibre Classification By Cross-sectionmentioning
confidence: 99%